The rights of victims of crime under Malaysian Law: legal framework and prospect for reforms - Hussin, Nasimah (Common Ground, 2010)

(untitled)
The rights of victims of crime should be protected. In conventional punitive justice as exercised in Malaysia, the law only focuses on punishment that is to be inflicted on the offender. Nevertheless, it ignores the needs of victims of crime. Even though the victim has certain rights, it does not mean that such rights can be obtained straight away. In fact, many victims neither realize nor understand about their rights. As a result, it is claimed, victims rarely experience justice when their case is dealt with by traditional punitive methods. Thus, it is timely to examine the existing legal framework and to suggest reform to the system so that the aspects relating to rights of crime victims can be formulated. This is significant in order to promote fair and just treatment for the parties concerned. This paper will focus on adequacy of law in protecting the rights of victims of crime in Malaysia.